If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10p + -9 = -5 Reorder the terms: -9 + 10p = -5 Solving -9 + 10p = -5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 10p = -5 + 9 Combine like terms: -9 + 9 = 0 0 + 10p = -5 + 9 10p = -5 + 9 Combine like terms: -5 + 9 = 4 10p = 4 Divide each side by '10'. p = 0.4 Simplifying p = 0.4
| X^2(x+2)(x+6)=0 | | 60x-500=0 | | 30/6=150/n | | 3/14//7/10 | | 110/500 | | 8+2(-10c+6)+3(5+-8)= | | 35x^2-20x-55= | | h(x)=3.5-3/4x | | 5y-4=62-6y | | f(x)=4x^2+16x+13 | | 200x+1=250x | | f(-2)=4+6+1 | | 7(3y+6)= | | 7(3+6)= | | b+4=2h-5 | | 5(b-2)=30 | | 4s+35=1 | | 9x+14=2x-17 | | -4q-10=-4q+10 | | 2.11+y=1.7 | | 5b-2b-8b= | | -4=2-14 | | 3h=37 | | .5(5-2x)=x/2 | | -5(-10+6q)=-3(10q+3) | | 2z-9=33 | | 3n+3=22 | | 6r+4s=2r+8 | | 2(8-2k)+12=-12 | | a^4-18a=-81 | | 13=2p+7 | | (3x^2-7x-3)-(2x^2+1)=x^2+11 |